Technologies and innovation : second International Conference, CITI 2016, Guayaquil, Ecuador, November 23-25, 2016, Proceedings /: second International Conference, CITI 2016, Guayaquil, Ecuador, November 23-25, 2016, Proceedings. (2016) - Unknown
No abstract available